Pengaruh Organisasi Pembelajaran, Keterlibatan Karyawan Terhadap Komitmen dan Perubahan Organisasi Di RSJPDHK - Asti Kuwaitiningsih; Iwan Kresna Setiadi; Acim Heri Iswanto (universitas Pamulang, 2021)
research which aims to determine the effect of organizational learning, employee involvement on commitment and organizational change is in a health institution, namely National Cardiovascular Center Harapan Kita located in Slipi, West Jakarta. The research uses quantitative research methods. Data collection was carried out through a survey of 100 respondents who were employees who worked at National Cardiovascular Center Harapan Kita. All respondents are samples that are spread across all work units using simple random sampling and the analysis technique is the PLS method. The results showed that 1) Organizational learning was not significant with a p value of 0.078 on organizational commitment. 2) Significant employee engagement variable with p value 0.00. 3) Organizational commitment itself has a significant effect with a p value of 0.024 on organizational change. 5) learning organization does not have a significant effect with a p value of 0.832 on organizational change. This study also concludes that nurse involvement has more influence on organizational change than learning organizations so that it is expected to increase employee engagement as a strategy for better change.